2008
DOI: 10.1523/jneurosci.4968-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Functional Peroxisomes from Mouse CNS Causes Dysmyelination and Axon Degeneration

Abstract: Peroxisomal metabolism is essential for normal brain development both in men and in mice. Using conditional knock-out mice, we recently showed that peroxisome deficiency in liver has a severe and persistent impact on the formation of cortex and cerebellum, whereas absence of functional peroxisomes from the CNS only causes developmental delays without obvious alteration of brain architecture.We now report that a substantial fraction of the latter Nes-Pex5 knock-out mice survive into adulthood but develop progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 45 publications
3
113
0
Order By: Relevance
“…As complete peroxisomal knockout mouse models cannot discriminate if functional disturbances in a tissue are locally generated or are caused by toxic metabolites produced elsewhere, conditional knockouts for one organ or cell type have been generated during the last few years. The functional deletion of peroxisomes in brain-specific Pex5 knockout mice results in a severe neuronal phenotype comprising demyelination and degeneration of axons (Hulshagen et al 2008). Nevertheless, this model could not resolve whether the absence of functional peroxisomes in neurons themselves was the cause of these damages or if disturbances in glial cells exerted the detrimental effect on neurons.…”
Section: Mysterious Degeneration: Impact Of Peroxisomes On Brain Funcmentioning
confidence: 99%
“…As complete peroxisomal knockout mouse models cannot discriminate if functional disturbances in a tissue are locally generated or are caused by toxic metabolites produced elsewhere, conditional knockouts for one organ or cell type have been generated during the last few years. The functional deletion of peroxisomes in brain-specific Pex5 knockout mice results in a severe neuronal phenotype comprising demyelination and degeneration of axons (Hulshagen et al 2008). Nevertheless, this model could not resolve whether the absence of functional peroxisomes in neurons themselves was the cause of these damages or if disturbances in glial cells exerted the detrimental effect on neurons.…”
Section: Mysterious Degeneration: Impact Of Peroxisomes On Brain Funcmentioning
confidence: 99%
“…For immunofluorescent stainings, mice were perfused with 10% neutral buffered formalin and sectioned into 10 lm frozen sections as previously described [17]. The following primary antibodies were used: glial acidic fibrillary protein (GFAP) (Sigma, Bornem, Belgium) and neuronal nuclei (NeuN) (Chemicon, Temecula, USA) raised in mice at a 1/100 dilution; catalase (Rockland, Gilbertsville, PA) and b-galactosidase (Cappel, CA, USA) raised in rabbits at a 1/ 100 and 1/400 dilution.…”
Section: Histochemistry and Immunohistochemistrymentioning
confidence: 99%
“…Furthermore, peroxisomal metabolism is essential for normal brain development. Studies on Pex5 knockout mice have revealed that peroxisomes provide oligodendrocytes with an essential neuroprotective function against axon degeneration, dysmyelination and neuroinflammation, which is relevant for human demyelinating diseases (Hulshagen et al 2008;Kassmann et al 2007).…”
Section: Mitochondrial and Peroxisomal Dynamics And Diseasementioning
confidence: 99%